Effectiveness of Collaborative Project-Based Learning to Improve Critical Thinking Science in Elementary School - salsadilla Maryan Ningsih; Ana Fitrotun Nisa; Akbar Al Masjid; Banun Havifah Khosiyono; Berliana Henu Cahyani (Postgraduate, University of Mataram, 2025)
The use of project-based collaborative models in learning can hone critical thinking skills in learning. The purpose of this study is to determine the implementation of collaborative project-based learning model innovations on the critical thinking skills of elementary school students in science lessons. The research method is a quasi-experiment with one-group pretest-posttest design. The data collection tool uses observation sheets for the implementation of learning models and critical thinking description tests. Indicators of critical thinking are inference, explanation, interpretation, and metacognition. The results of the research obtained in the form of a collaborative project-based learning model ran very well in phase one 92% and phase two 100%. There was an increase in the average pretest score of 56.73 and posttest of 91.57. The results of the effect size test (cohen'd) showed a very high category of 5.94, in the very high category. It can be concluded that collaborative project-based learning models are very effective in improving critical thinking in elementary school science.